2017
DOI: 10.3390/hydrology4020020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Predictability of the Hydrological Response of Mountain Catchments to Heavy Rain on Snow Events: A Case Study in the Spanish Pyrenees

Abstract: From 18 to 19 June 2013, the Ésera river in the Pyrenees, Northern Spain, caused widespread damage due to flooding as a result of torrential rains and sustained snowmelt. We estimate the contribution of snow melt to total discharge applying a snow energy balance to the catchment. Precipitation is derived from sparse local measurements and the WRF-ARW model over three nested domains, down to a grid cell size of 2 km. Temperature profiles, precipitation and precipitation gradient are well simulated, although wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 81 publications
1
28
0
Order By: Relevance
“…Our finding that net radiation is responsible for slightly more ROS snowmelt in the western United States than turbulent heat fluxes is consistent with the conclusion in Mazurkiewicz et al (2008), but differs with other studies (e.g., Corripio & López-Moreno, 2017;Marks et al, 1998) that find that turbulent heat fluxes dominate. The difference between our study and those referenced above may be explained by the fact that we investigate ROS with a different perspective.…”
Section: /2019wr024950supporting
confidence: 70%
“…Our finding that net radiation is responsible for slightly more ROS snowmelt in the western United States than turbulent heat fluxes is consistent with the conclusion in Mazurkiewicz et al (2008), but differs with other studies (e.g., Corripio & López-Moreno, 2017;Marks et al, 1998) that find that turbulent heat fluxes dominate. The difference between our study and those referenced above may be explained by the fact that we investigate ROS with a different perspective.…”
Section: /2019wr024950supporting
confidence: 70%
“…During a ROS, the addition of snowmelt water to the water from rainfall is an important contributor or even the triggering mechanism of floods in temperate and cold environments. Such is the case of mountains in North America [10,15,59], and the Alps [12], or the Pyrenees [14] in Europe. Moreover, the antecedent soil moisture is usually higher on snow-covered slopes from the infiltration of meltwater into the soil during the snow season, further facilitating the occurrence of a flood during a ROS event [11].…”
Section: Resultsmentioning
confidence: 99%
“…The warmer than freezing air temperature that causes precipitation to fall in a liquid state may melt snow, and that meltwater combined with the water from rainfall can trigger increased surface runoff and as a consequence flooding. While a ROS does not necessarily generate river flooding, major floods associated with ROS have been reported in the mountains of Western United States [9,10], in Southern Germany [11], Switzerland [12], Austria [13], the Spanish Pyrenees [14], or the Canadian Rockies [15]. Morán-Tejeda et al [16] demonstrated the relevance of elevation and seasonality for ROS to occur; in Switzerland they peak at elevations between 800-1200 m in winter and between 1800-2600 m in spring and summer, highlighting the importance of considering snowmelt, together with the amount of rain, when forecasting river flooding in mountain areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors focus their research on the forecasting of melting processes and their consequences. Corripio and López-Moreno [35] performs prediction studies about thawing processes happening in the Spanish Pyrenean chain, which is the research location area of our article. In other cases, the studies focus on urbanized areas such as that of Berezowski and Chybicki [36], where the effect of snow melting on discharge forecasts is highlighted by carrying out a study in an urbanized basin clearly influenced by snow processes increasing the runoff.…”
Section: Introductionmentioning
confidence: 99%